2020
DOI: 10.1128/mbio.00532-20
|View full text |Cite
|
Sign up to set email alerts
|

RhlR-Regulated Acyl-Homoserine Lactone Quorum Sensing in a Cystic Fibrosis Isolate of Pseudomonas aeruginosa

Abstract: The opportunistic pathogen Pseudomonas aeruginosa is a leading cause of airway infection in cystic fibrosis (CF) patients. P. aeruginosa employs several hierarchically arranged and interconnected quorum sensing (QS) regulatory circuits to produce a battery of virulence factors such as elastase, phenazines, and rhamnolipids. The QS transcription factor LasR sits atop this hierarchy and activates the transcription of dozens of genes, including that encoding the QS regulator RhlR. Paradoxically, inactivating lasR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 68 publications
10
99
0
Order By: Relevance
“…RhlR plays other important roles in host interactions ( 75 ) which may benefit P. aeruginosa LasR− strains. The observation that rhlR mutants are rare in natural isolates and that LasR− strains with active RhlR are virulent ( 25 , 76 ) underscores the relevance of this mechanism and highlights the importance of understanding how microbial interactions influence RhlR activity.…”
Section: Discussionmentioning
confidence: 99%
“…RhlR plays other important roles in host interactions ( 75 ) which may benefit P. aeruginosa LasR− strains. The observation that rhlR mutants are rare in natural isolates and that LasR− strains with active RhlR are virulent ( 25 , 76 ) underscores the relevance of this mechanism and highlights the importance of understanding how microbial interactions influence RhlR activity.…”
Section: Discussionmentioning
confidence: 99%
“…Damkiaer and colleagues observed that a single rpoD mutation induced alginate overproduction only in a particular genetic background of the DK2 lineage and, thus, was positively selected [62]. Genic alterations of mexT were shown to compensate the effects of lasR inactivation, suggesting that positive selection of this mutation may be promoted in lasR-negative isolates [63][64][65][66]. In the same way, mutations reverting the mutator phenotype might be positively selected only after alteration of the genes from DNA repair systems [8].…”
Section: Accumulation Of Mutations Relies On Selection Mechanismsmentioning
confidence: 99%
“…Deletion of either LasRI and RhlRI systems can be complemented by restoring a functional protein or in the case of the synthases protein (lasI and rhlI) by exogenous autoinducer molecules 48,49 . Recent studies have elegantly demonstrated evolutionary trajectories for LasR null mutants where a functional RhlRI system independent of LasRI quickly emerges [48][49][50] . This was an interesting finding considering the QS hierarchy puts lasR at the top of the QS system with the LasRI activated complex inducing expression of the rhlR regulator.…”
Section: P Aeruginosa Cf Isolate Pa80 Is a Rhlri Mutantmentioning
confidence: 99%